Research Progress in Small-Molecule Detection Using Aptamer-Based SERS Techniques - Li Zheng; Qingdan Ye; Mengmeng Wang; Fan Sun; Qiang Chen; Xiaoping Yu; Yufeng Wang; Pei Liang (Biosensors)
Nucleic acid aptamers are single-stranded oligonucleotides that are selected through exponential enrichment (SELEX) technology from synthetic DNA/RNA libraries. These aptamers can specifically recognize and bind to target molecules, serving as specific recognition elements. Surface-enhanced Raman scattering (SERS) spectroscopy is an ultra-sensitive, non-destructive analytical technique that can rapidly acquire the “fingerprint information” of the measured molecules. It has been widely applied in qualitative and trace analysis across various fields, including food safety, environmental monitoring, and biomedical applications. Small molecules, such as toxins, antibiotics, and pesticides, have significant biological effects and are harmful to both human health and the environment. In this paper, we mainly introduced the application and the research progress of SERS detection with aptamers (aptamer-based SERS techniques) in the field of small-molecule detection, particularly in the analysis of pesticide (animal) residues, antibiotics, and toxins. And the progress and prospect of combining the two methods in detection were reviewed.